ANALISA PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DAN LOYALITAS NASABAH PADA SALAH SATU BANK SWASTA DI JAKARTA - Tashia Augusta Schuurman (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. Banking at the present time is required to further improve its service,whereas customers are increasingly improving their mobility and needs. Servicein the banking industry is a very important thing in determining their success inthe face of competition. Quality of service is very influential on customersatisfaction and loyalty. The existence of decrease in the number of customers, adecrease in the amount of good incomes from savings, deposits and loans, also anincrease in the number of customers who complain significantly occur at thisprivate bank. This study was conducted to determine the effect of service qualityon customer satisfaction and loyalty on one Private Bank branches in CentralJakarta. The respondent in this study are the customers of the private bank inCentral Jakarta branch where the total number of customer at the private bankbranch in Central Jakarta are as many as 112 customers. The number ofrespondents in this study set out 88 respondents using a sampling technique calledpurposive sampling with slovin formula. This study uses analysis with the help ofthe SMART PLS program to determine the effect between service quality,customer loyalty and customer satisfaction, in addition, this study also uses thePearson r correlation with SPSS to determine the relationship between eachdimension. The results obtained from this study show that: 1) the quality ofservice gives positive and significant effect on customer satisfaction, 2) thecustomer satisfaction does not give positive and significant effect on customerloyalty, 3) the quality of service gives positive and significant effect on customerloyalty. The recommendation for this private bank in Central Jakarta branch is toimprove the quality of services provided to customers starting from theimprovement of the employee's performance, system improvement, andtechnology improvement so that the customer is satisfied and loyal to this privatebank.Keywords: Service Quality, Customer Satisfaction, Customer Loyalty, SMARTPLS